Size Dependence of Electrical Conductivity and Thermoelectric Enhancements in Spin‐Coated PEDOT:PSS Single and Multiple Layers. (20th January 2017) - Andrei, Virgil; Bethke, Kevin; Madzharova, Fani; Beeg, Sebastian; Knop‐Gericke, Axel; Kneipp, Janina; Rademann, Klaus
Abstract : This work reveals that the electrical conductivity σ of a poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) film can be significantly increased by spin‐coating multiple thin layers onto a substrate. Generally, σ can be improved by more than fourfold for multiple layers, as compared to a single thicker one. A gradual enhancement is observed for pristine PEDOT:PSS films (up to 2.10 ± 0.26 S cm –1 for five‐layered films), while a plateau in σ at around 200 S cm –1 is reached after only three layers, when using a PEDOT:PSS solution with 5 vol% dimethyl sulfoxide. By contrast, only a small change in σ is observed for single layers of varying thickness. Accordingly, the thermoelectric power factor is also increased by up to 3.4 times for the multiple layers. Based on atomic force microscopy, X‐ray photoelectron spectroscopy, UV–vis, and Raman spectroscopy measurements, two mechanisms are also proposed, involving an increase in percolation by inclusion of smaller grains within the existing ones, respectively, a reorganization of the PEDOT:PSS chains. These findings represent a direct strategy for enhancing the thermoelectric performance of conductive polymer films without additional reagents, while the mechanistic insights explain existing literature results. Abstract : The electrical conductivity (σ) of thermoelectric poly(3, 4‐ethylenedioxythiophene): poly(styrenesulfonate) films is investigated as a function of the film thickness. A fourfold enhancement in σ is obtained by spin‐coating several thin layers, instead of a single thicker one. Two plausible models can explain the improvement, involving a reorganization of the polymer chains and an increase in percolation between the polymer grains.